VCSEL design for high power, densely packed arrays - Kolb, Johanna S.; Engelhardt, Andreas; Gerlach, Philipp; Jager, Roland; Monch, Holger; Weichmann, Ulrich; Witzigmann, Bernd (2013 IEEE Photonics Conference, IPC 2013, 2013)
We utilize high power VCSEL arrays for several applications where high efficiency especially at high operating temperatures is essential. Our approach to design VCSEL devices optimized for the requirements of these applications is presented. © 2013 IEEE.
CRIS-Team Scopus Importer:2021-06-11